Comprehensive Analysis and Production of Powdered Starter Using Saccharomyces cerevisiae YM45 - Su Jeong Lee; Joo-Yeon Kim; So-Young Kim; Soo-Hwan Yeo; Chan-Woo Kim (Fermentation)
In order to secure domestic microbial resources, a fruit-flavored yeast was selected, and a starter manufacturing technology was developed to evaluate its quality characteristics. Among 26 yeast strains analyzed using an electronic nose, Saccharomyces cerevisiae YM45 isolated from Makgeolli was identified as having high levels of methyl formate and propan-2-one, compounds that are associated with fruity and sweet aroma. A powdered starter was then produced with S. cerevisiae YM45, and its quality characteristics were analyzed. When cyclodextrin was used as an excipient, with water content at 4.7%, bacterial contamination was found to be 2.30 log CFU/g, which ensures quality and safety. The rehydration rate, assessed using a PBS buffer, showed a high survival rate of 8.7 log CFU/g, which is a suitable condition for preserving yeast activity. These findings suggest that domestically sourced microbial resources can serve as viable alternatives to imported strains, with potential applications in industrial fermentation.